Thiolactone chemistry and copper-mediated CRP for the development of well-defined amphiphilic dispersing agents. Issue 8 (28th January 2016) - Driessen, Frank; Herckens, Roald; Espeel, Pieter; Du Prez, Filip E.
Abstract : A straightforward synthetic pathway was developed for the synthesis of amphiphilic graft and toothbrush copolymers by combining copper-mediated controlled radical polymerization with the thiolactone-based amine–thiol–ene conjugation in a "grafting-onto approach". Abstract : A straightforward synthetic pathway was developed for the synthesis of amphiphilic graft and toothbrush copolymers by combining copper-mediated controlled radical polymerization with the thiolactone-based amine–thiol–ene conjugation in a "grafting-onto approach". First, a series of well-defined, thiolactone containing macromolecular backbones were synthesized via copolymerization with a thiolactone-containing monomer. Next, acrylate end-functionalized polymers were obtained in a post-polymerization modification procedure and coupled to the backbones. Furthermore, in-depth characterization of the different structures was performed by the use of SEC, NMR, MALDI-TOF and LCxSEC analysis. In order to demonstrate the amphiphilic behaviour of these graft and toothbrush copolymers, micelle formation tests were carried out and measured with DLS and TEM, while the dispersing features of these comb-like copolymers were evaluated by pigment stabilization tests.